A case study of the effectiveness of the grain direct subsidy policy– Empirical evidence from hubei province in China. Issue 5 (1st November 2016) - Xiao, Qin; Xiao, Lei; Liu, Yaxin
Abstract: In this paper, a dynamic general equilibrium model has been established to analyze grain direct subsidies. The ordered logistic model based on the random sample in rural areas across Hubei province in China has been established and the result shows: if the government issues subsidies only according to the acreage of land a farmer owns, but not the planting area that a farmer uses for production, the current grain direct subsidy policy can only improve farmers' welfare and it can not improve grain output observably.